2010
DOI: 10.1038/nbt.1604
|View full text |Cite
|
Sign up to set email alerts
|

Real-time imaging of hepatitis C virus infection using a fluorescent cell-based reporter system

Abstract: Hepatitis C virus (HCV), which infects 2-3% of the world population, is a causative agent of chronic hepatitis and the leading indication for liver transplantation1. The ability to propagate HCV in cell culture (HCVcc) is a relatively recent breakthrough, and a key tool in the quest for specific antiviral therapeutics. Monitoring HCV infection in culture generally involves bulk population assays and/or terminal processing of potentially precious samples. Live-cell imaging avoids this, but necessitates genetica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
282
1
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 238 publications
(296 citation statements)
references
References 33 publications
(41 reference statements)
12
282
1
1
Order By: Relevance
“…To this end, we infected a population of Huh-7.5 cells with an HCVcc (H77/JFH chimera) (18) at a high multiplicity of infection and confirmed that Ͼ99% were HCV NS5A positive by immunofluorescence staining (data not shown). These "donor cells" were cocultured with Huh-7.5 or clone#1 "target cells" that had additionally been transduced with a reporter construct in which HCV infection is detected at the single-cell level in living cells by relocation of the red fluorescent protein tagRFP from a mitochondrial (uninfected) to a nuclear (infected) localization (22). In addition, target cells were transduced to express mock or different OCLN variants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, we infected a population of Huh-7.5 cells with an HCVcc (H77/JFH chimera) (18) at a high multiplicity of infection and confirmed that Ͼ99% were HCV NS5A positive by immunofluorescence staining (data not shown). These "donor cells" were cocultured with Huh-7.5 or clone#1 "target cells" that had additionally been transduced with a reporter construct in which HCV infection is detected at the single-cell level in living cells by relocation of the red fluorescent protein tagRFP from a mitochondrial (uninfected) to a nuclear (infected) localization (22). In addition, target cells were transduced to express mock or different OCLN variants.…”
Section: Resultsmentioning
confidence: 99%
“…A subfraction of the donor cells was fixed and stained for NS5A to confirm that Ͼ99% of cells were HCV positive. Target cells were transduced with the pTRIP-tagRFP-NLS-IPS1 reporter construct recently described by Jones and colleagues (22). Briefly, this construct contains a fusion protein of the red fluorescent protein tagRFP, a simian virus 40 (SV40) nuclear localization sequence (NLS), and the C-terminal part (amino acids 462 to 540) of the interferon-␤ promoter stimulator protein 1 (IPS1).…”
Section: Methodsmentioning
confidence: 99%
“…[85] (see Table 1) is particularly amenable to investigate cell-to-cell transmission [85,102,188] as it allows at the same time distinguishing two different cell populations (producer and target cells) and tracking rare infection events at the single cell level. As an alternative to using two cell populations, counting the number of cells per infection focus after culture under an agarose overlay has been used as an estimate of cell-to-cell transmission efficiency [171,189].…”
Section: Cell-to-cell Transmissionmentioning
confidence: 99%
“…Rare reports of infection with HCVsp. Autofluorescence hinders immunofluorescence assays [85] (Haid and Pietschmann, personal communication). Reviewed by [86]).…”
Section: Namementioning
confidence: 99%
“…Recently, a real-time imaging of HCV infection using a fluorescent cell-based reporter system has been described [20]. In this system a cellular marker of HCV infection was constructed based on a known substrate of the NS3/4A protease, the mitochondrially tethered interferon (IFN)-b promoter stimulator protein 1 (IPS-1).…”
Section: Introductionmentioning
confidence: 99%